Optimizing Energy Efficiency and User Comfort Through Smart Lighting Controls - Zahraa M. Kassem Alasady (Technium Electro, 2025)
Smart lighting controls have emerged as an effective means of reducing energy use in buildings while ensuring occupant comfort. This study evaluates a two-floor, 12-room case using three layered strategies: occupancy sensing, daylight harvesting, and adaptive task-tuning. Lighting demand was estimated through the lumen method and applied to an annual mixed-use operating schedule. Results show that occupancy sensing delivers the largest single reduction at about 25%, while daylight harvesting contributes an additional 10.5% and task-tuning adds a further 10%. Combined, the strategies reduce lighting energy use by nearly 40%, equivalent to avoiding 0.45–0.56 tonnes of CO₂ per year based on current grid emission factors in Iraq. Beyond energy savings, the controls help maintain recommended illuminance levels of 300–500 lux, limit glare, and improve user satisfaction by creating adaptable lighting conditions. The findings demonstrate that layered control systems are far more effective than isolated measures, providing both environmental benefits and occupant comfort. The approach presented here offers a practical and replicable framework for integrating smart lighting technologies into sustainable building design and operation.